Analisis Transformasi Struktur Ekonomi 7 Provinsi di Wilayah Jawa dan Bali (Pendekatan LQ dan Shift Share) - Haryanto (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2021)
This study is aimed to: (a) analyze changes in the economic structure of Java and Bali from 2010 to 2019, (b), understand to what extent the level of specialization of economic sectors in the Java and Bali Region that utilizes the base or the leading sector, and (c) understand on economic sectors that are growing progressively and have high competitiveness in the Java and Bali Regions. This study uses the LQ method and shift share analysis. Results show that the economy of Java-Bali from 2010 to 2019 did not experience much shift in the economic structure. In general, sectors that became the source of growth in 2010 in each province in Java-Bali remained the base sector/sources of growth in 2019. The shift share analysis shows that the Manufacturing sector in most provinces in Java-Bali is in quadrant III, which means that it grows slowly and its commodities lack of competitiveness. Meanwhile, the Communication and Information sector is mostly in quadrant II, which means this sector is growing progressively but lacks of competitiveness. Likewise with the Transportation and Warehousing sector, in most provinces this sector is able to grow progressively, but this sector lacks good competitiveness (quadrant II). On the other hand, the Service sectors in most provinces have grown progressively and have good competitiveness (quadrant I). The implication of this finding is the presence of symptoms of premature deindustrialization in Java-Bali, since the Services sector is growing faster, more progressive with a contribution to GDRP exceeds the Manufacturing sector, whereas the Manufacturing sector is not mature yet. Premature deindustrialization in Java-Bali has the potential to reduce job creation in the manufacturing sector and increase the risk of unemployment. Although the Service sector is growing progressively and competitively; However, if we look at the labor productivity, it appears that the labor productivity of the Service sector is much smaller than the labor productivity of the Manufacturing sector